Influence of sewage disposal on the water quality of the Sucuru River alluvial aquifer in the municipality of Sumé-PB, Brazil - Salgado,Jaqueline Pereira (2018)
ABSTRACT The objective of this study was to evaluate the influence of sewage discharge on the quality of the water exploited from the Sucuru River alluvial aquifer, located in the municipality of Sumé, Paraíba state, Brazil. The study was based on physical-chemical and microbiological analyses of the waters from nine wells located along the alluvium. The results of the indicators showed that the alluvial aquifer studied has the capacity to filter and disperse pollutants. It is possible to observe a gradual reduction of chlorides, chemical oxygen demand and total dissolved solids along the alluvial perimeter. Thus, urban sewage becomes a source of water recharge with potential to be reused. We concluded that the utilization of water from this type of aquifer, which has been intensified in recent dry years, can be established in a safe and sustainable way. However, a strict monitoring plan for controlling recharge groundwater levels is highly necessary. Further studies in this direction should lead to a model of adequate use of this system, which can be reproduced in the Brazilian semi-arid region.